Piperlongumine Is an NLRP3 Inhibitor With Anti-inflammatory Activity - Shi, Jie; Xia, Yang; Wang, Huihong; Yi, Zhongjie; Zhang, Ruoruo; Zhang, Xiufeng (Frontiers in Pharmacology, 2022)
Piperlongumine (PL) is an alkaloid from Piper longum L. with anti-inflammatory and antitumor properties. Numerous studies have focused on its antitumor effect. However, the underlying mechanisms of its anti-inflammation remain elusive. In this study, we have found that PL is a natural inhibitor of Nod-like receptor family pyrin domain-containing protein-3 (NLRP3) inflammasome, an intracellular multi-protein complex that orchestrates host immune responses to infections or sterile inflammations. PL blocks NLRP3 activity by disrupting the assembly of NLRP3 inflammasome including the association between NLRP3 and NEK7 and subsequent NLRP3 oligomerization. Furthermore, PL suppressed lipopolysaccharide-induced endotoxemia and MSU-induced peritonitis in vivo, which are NLRP3-dependent inflammation. Thus, our study identified PL as an inhibitor of NLRP3 inflammasome and indicated the potential application of PL in NLRP3-relevant diseases.